Comparison of Lipid Profile between Small for Gestational Age and Appropriate for Gestational Age Babies in a Tertiary Level Hospital in Bangladesh - Islam, Tithi; Ghosh, Uzzal Kumar; Sufian, Abu; Sharmin, Mowmita; Akhter, Naima; Ali, Md Ayub; Hossain, Md Abir; Ahmed, ATM Faruque; Bhuiyan, Mizanur Rahman (Eastern Medical College Journal, 2022)
Background: Coronary heart disease is a common cause of morbidity and mortality. Dyslipidemia is one of the risk factors of coronary vascular disease. Many patients have been seen coronary artery disease with dyslipidemia with a history of intrauterine growth retardation and low birth weight (LBW). Lipid profile at the start of life broadens the understanding of dyslipidemia and their association with coronary heart disease in later life. This study will help to identify high-risk babies at birth and preventive management of the disease. So, the study was conducted to compare the serum lipid profile between small for gestational age (SGA) and appropriate for gestational age (AGA) babies. Methodology: A cross-sectional study was conducted at Mymensingh Medical College and Hospital. A total of 50 cases of SGA babies and another 50 of AGA were taken as a control according to selection criteria. Information was collected by detailed history, clinical examination, and follow up by using a pre-designed questionnaire. A lipid profile was done in both groups. Then the lipid profile between the two groups were compared. Results: Serum total cholesterol (TC), LDL, and triglyceride (TG) were significantly higher in terms SGA, preterm SGA as well as SGA babies than term AGA, preterm AGA as well as AGA babies. Only TC was seen significantly higher in LBW babies than NBW babies. Regarding HDL level, no significant difference was found between term SGA, preterm SGA as well as SGA babies and term AGA, preterm AGA as well as AGA babies. And no significant difference was found in the lipid profile values between male and female newborns. Conclusion: This study concludes that serum lipid levels are higher in SGA neonates. It may have a great impact on the future life of these newborns which needs long term to follow up. Eastern Med Coll J. Jan 2023; 8 (1) 6-11